Chemiluminescent Nitrogen Detection (CLND) to Measure Kinetic Aqueous Solubility. Issue 4 (16th December 2013) - Kestranek, Aimee; Chervenak, Andrew; Longenberger, Justin; Placko, Steven
Abstract: Solubility is the dose‐limiting property for in vitro studies, and therefore is a critical physicochemical property to measure in drug discovery. Solubility data can be used to guide lead optimization, troubleshoot erratic bioassay results, and identify potential downstream liabilities such as insufficient solubility for bioassays or oral bioavailability. Typically, early in vitro studies are performed using library compounds prepared as dimethylsulfoxide (DMSO) stock solutions, resulting in in vitro test solutions containing DMSO at low concentration (<5% v/v). Since DMSO can affect the apparent solubility, it is desirable to obtain solubility data under conditions mimicking the in vitro study. Kinetic solubility (from DMSO stock solutions) is often preferred over thermodynamic solubility (from dry powder) in early drug discovery. The protocols in this article describe a general procedure for assessing kinetic aqueous solubility of early drug discovery compounds using a miniaturized shake flask method with chemiluminescent nitrogen detection (CLND). Curr. Protoc. Chem. Biol . 5:269‐280 © 2013 by John Wiley & Sons, Inc.